Factors affecting usage of computer in construction industry. - Wong, Lai Chan. (2009)
This report attempts to study how information technology can be used to support regionalisation of the construction industry. The focus will be on the use of IT to enhance the export of construction services to the region. In particular, the report will look into how the design and engineering phase of a construction project can be improved to increase in labour productivity and in cost competitiveness of Singapore construction services.